2011
DOI: 10.1177/1045389x11409081
|View full text |Cite
|
Sign up to set email alerts
|

A Two-Level Approach for the Optimal Design of Morphing Wings Based On Compliant Structures

Abstract: The great interest in developing morphing airfoils is mainly based on their capability to adapt their shape to optimize some specific aircraft performance indices during the mission. Nevertheless, the design of these kinds of devices requires the availability of ad hoc-developed procedures able to tackle the conflicting requirements such as the high deformability requested to change the airfoil shape coupled to the load-carrying capability and to the low weight.The article proposes an approach for optimal airf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
73
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(73 citation statements)
references
References 58 publications
0
73
0
Order By: Relevance
“…12 De Gaspari and Ricci present a two level optimization routine for morphing camber design using FSI and genetic algorithms. 13 Daynes and Weaver show a staged FSI analysis of a morphing wind turbine blade wherein the static solution is first found without aerodynamic loading, after which the aerodynamic load was applied and the code run again until convergence. 8 Molinari et al 14 and Thuwis, Abdalla, and Gurdal 15 also present related FSI analyses for morphing aircraft applications.…”
mentioning
confidence: 99%
“…12 De Gaspari and Ricci present a two level optimization routine for morphing camber design using FSI and genetic algorithms. 13 Daynes and Weaver show a staged FSI analysis of a morphing wind turbine blade wherein the static solution is first found without aerodynamic loading, after which the aerodynamic load was applied and the code run again until convergence. 8 Molinari et al 14 and Thuwis, Abdalla, and Gurdal 15 also present related FSI analyses for morphing aircraft applications.…”
mentioning
confidence: 99%
“…It is found that the deformed shapes of the adaptive aerofoils can be significantly affected by the pressure loads and the actuation requirement can be reduced by exploiting the aerodynamic effects. Gaspari et al(2011) proposed a two-level optimization approach to determine the optimal deformed aerofoil shape. The optimization method consisted of two steps: the first step is an optimization approach to select optimal deformed shapes which are used as targets to then identify the topology design of the internal structure in the second optimization step.…”
Section: Optimization Designmentioning
confidence: 99%
“…(De Gaspari et al, 2011;Molinari et al, 2011;Bae et al, 2005;Molinari et al, 2015) A multi-disciplinary morphing structures design optimization methodology was developed by Monlinari et al (2011) capable of concurrently optimizing aerodynamic and structural parameters from the very beginning of the interactions between aerodynamics, structures and control theory and applied to a morphing structure design case. The optimization method enables assessment of the effects of the strong coupling between the structure and aerodynamic loads.…”
Section: Optimization Designmentioning
confidence: 99%
“…In the 21 st century, developments in material science, need of adaptive internal structures and lightweight actuation systems force researchers to study computational modeling and simulation of a novel reconfigurable aero-servo-elastic system [8]. From that point of view, one can conclude that airfoil profile adjustment is still a big problem waiting for an acceptable solution.…”
Section: Introductionmentioning
confidence: 99%